Relationship of dentist instructions, patient knowledge and experience to the level of compliance of patients after tooth extraction: Study cross-sectional - Adhani, Rosihan; Fitrian, Muhammad Soni; Nurrahman, Tri; Sari, Galuh Dwinta; Wardani, Ika Kusuma (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: The incidence of tooth decay in Banjarmasin City is 37.62% and the rate of tooth extraction is 9.42%. Tooth extraction is removing the whole tooth or root from its socket which involves hard tissue and soft tissue in the oral cavity. One important factor that influences the wound healing process after tooth extraction is the patient's compliance with the instructions given by the dentist. This study aimed to analyze the correlation between dentist instructions, patient’s knowledge, and patient’s experience on the level of patient’s compliance after tooth extraction. Methods: The study used an analytical method with a cross sectional approach with a non-probability sampling technique, purposive sampling with a total sample of 33 people. The inclusion criteria were: post-tooth extraction patients at the Oral Surgery Dental Clinic of Gusti Hasan Aman Dental and Oral Hospital, aged 18-60 years, maximum tooth extraction in the last 3 months, patients extracted with the intra alveolar method, and patients without systemic diseases. A questionnaire was used and the data results were analyzed using SPSS with correlative analytical methods. Results: The instructions given by the dentist were very clear by 32 patients (97%); the knowledge of the patients was very good, as many as 31 patients (93.9%); the patients had very good experience, as many as 26 patients (78.9%), and the level of patient compliance with post-extraction instructions was from 33 people (100%). There is a relationship between dentist instructions on the level of patient compliance with a correlation value of 0.053 (strong relationship level) and there is a relationship between patient knowledge and patient compliance with a correlation value of 0.514 (strong relationship level). Conclusion: Dentist instructions and patient’s knowledge are related to the level of patient compliance while experience has no correlation with the level of patient compliance. Complications and impaired wound healing can be minimized by increasing the effectiveness of instructions to patients.KEY WORDS: Dentist's instructions, knowledge, experience, level of compliance, complication.Korelasi instruksi dokter gigi, pengetahuan dan pengalaman pasien terhadap tingkat kepatuhan pasien pasca ekstraksi gigi: Studi cross-sectionalABSTRAK Pendahuluan: Kasus kerusakan gigi di Kota Banjarmasin sebesar 37,62% dan angka ekstraksi gigi yaitu 9,42%. Ekstraksi gigi merupakan tindakan pencabutan gigi utuh atau akar gigi dari soketnya yang melibatkan jaringan keras dan jaringan lunak dalam rongga mulut. Salah satu faktor penting yang memengaruhi proses penyembuhan luka pasca ekstraksi gigi yaitu kepatuhan pasien terhadap instruksi yang diberikan oleh dokter gigi. Tujuan penelitian ini menganalisis korelasi instruksi dokter gigi, pengetahuan pasien, dan pengalaman pasien terhadap tingkat kepatuhan pasien pasca ekstraksi gigi. Metode: Penelitian menggunakan metode analitik dengan pendekatan cross sectional dengan teknik non-probability sampling, purposive sampling dengan jumlah sampel 33 orang. Kriteria inklusi yaitu pasien pasca ekstraksi gigi di Poli Gigi Bedah Mulut Rumah Sakit Gigi dan Mulut Gusti Hasan Aman usia 18-60 tahun, maksimal ekstraksi gigi 3 bulan terakhir, pasien yang diekstraksi dengan metode intra alveolar, dan pasien tanpa penyakit sistemik. Alat penelitian adalah kuesioner dan hasil datanya dianalisis dengan menggunakan SPSS dengan metode analitik korelatif. Hasil: Instruksi yang diberikan dokter gigi sangat jelas diterima oleh 32 pasien (97%). Pengetahuan yang dimiliki pasien sangat baik sebanyak 31 pasien (93,9%), pasien mempunyai pengalaman yang sangat baik sebanyak 26 pasien (78,9%), dan tingkat kepatuhan pasien terhadap instruksi pasca ekstraksi sebanyak 33 orang (100%). Terdapat hubungan antara  instruksi dokter gigi terhadap tingkat kepatuhan pasien dengan nilai korelasi 0,053 (tingkat hubungan yang kuat) dan terdapat hubungan antara pengetahuan pasien terhadap tingkat kepatuhan pasien dengan nilai korelasi 0,514 (tingkat hubungan kuat). Simpulan: Instruksi dokter gigi dan pengetahuan pasien berhubungan dengan tingkat kepatuhan pasien sedangkan pengalaman tidak memiliki hubungan dengan tingkat kepatuhan pasien. Komplikasi dan gangguan penyembuhan luka dapat diminimalisir dengan meningkatkan efektifitas instruksi kepada pasien.   KATA KUNCI: instruksi dokter gigi, pengetahuan, pengalaman, tingkat kepatuhan, komplikasi.